Pengembangan Model Pembelajaran GAP Pada Permainan Bola Voli di Kelas V Sekolah Dasar - Galuh Agus Permadi; Selvi Atesya Kesumawati; Dewi Septaliza; I Bagus Endrawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to develop a GAP-based learning model (Visuals, Auditory, and Practice) for volleyball material for fifth-grade elementary school students. The study employed the Research and Development (R&D) method using the ADDIE approach (Analysis, Design, Development, Implementation, and Evaluation). This method was used to develop the GAP-based learning model in order to improve the effectiveness of learning at SD Negeri 03 Gumawang. The results of the study indicate that this model has high validity and effectiveness. Expert validation showed a Content Validity Ratio (CVR) score of 0.9, which falls into the valid category, covering aspects of content, language, presentation, and alignment with learning objectives. Its effectiveness was measured through student questionnaires after implementation, resulting in an effectiveness score of 86%. The GAP model integrates visual images for technique visualization, audio guidance for instructions, and direct practice for skill application. This approach not only enhances theoretical understanding but also improves students’ motor skills. The model is designed to accommodate various learning styles, including visual, auditory, and kinesthetic, while also encouraging collaboration and social skills through group activities. Through a direct practice-based approach, the model effectively improves students’ psychomotor skills and provides meaningful learning experiences. The GAP model can also be applied to other subjects to improve the quality of learning at the elementary school level. Keywords: Volleyball, GAP, Physical Education, Elementary School